The results of mathematics learning management exploration of basic counting by applying problem-based learning activities (PBL) and exploration Learning Management (5E) for Mathayomsuksa 4 Students at Prince of Songkla University Demonstration School (Secondary) - Ninchim, Suthatip; Tunya, Napaporn (Wishing Journal Review, 2021)
The purposes of this study were 1) to develop Mathematics learning methods activities using Problem-Based Learning (PBL) and exploration Learning Management (5E) for Mathayomsuksa 4 Students to achieve the score of 75% 2) to compare students’ achievement before and after learning 3) to study student's satisfaction regarding the learning management. The sample group was selected randomly of 29 Mathayomsuksa 4/1. The tools used in the research were 1) lesson plans by using Problem-Based Learning (PBL) and exploration Learning Management (5E) activities of basic counting principles 2) learning achievement test 3) the satisfaction questionnaire for management of instructional activities. Statistics used in data analysis are the average, deviation standard and test the hypothesis using t – test for One Sample. Research results were as follow: The management method of instructional activities of basic counting principles in Mathematics using Problem-Based Learning (PBL) and exploration Learning Management (5E) of Mathayomsuksa 4 Students has achieved criterion learning score of 75% The average score of Pre-learning achievement is higher than the average score of Post-learning achievement with a statistically significant level of .05 3) The overall satisfaction of students after the learning management was at the highest level. ( X = 4.59, SD = .49)